Self-cleaning properties in engineered sensors for dopamine electroanalytical detection1. Issue 5 (7th March 2015) - Soliveri, Guido; Pifferi, Valentina; Panzarasa, Guido; Ardizzone, Silvia; Cappelletti, Giuseppe; Meroni, Daniela; Sparnacci, Katia; Falciola, Luigi
<x xml:space="preserve">Abstract</x> A self-cleaning reusable composite electrode is ad hoc designed to bypass the fouling problem connected with biomedical molecule detection (e.g. dopamine).